2016
DOI: 10.7883/yoken.jjid.2015.137
|View full text |Cite
|
Sign up to set email alerts
|

Pentagalloylglucose Blocks the Nuclear Transport and the Process of Nucleocapsid Egress to Inhibit HSV-1 Infection

Abstract: SUMMARY: Herpes simplex virus type 1 (HSV-1), a widespread virus, causes a variety of human viral diseases worldwide. The serious threat of drug-resistance highlights the extreme urgency to develop novel antiviral drugs with different mechanisms of action. Pentagalloylglucose (PGG) is a natural polyphenolic compound with significant anti-HSV activity; however, the mechanisms underlying its antiviral activity need to be defined by further studies. In this study, we found that PGG treatment delays the nuclear tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 30 publications
1
22
0
Order By: Relevance
“…Interestingly, pentagalloylglucose (PGG), a natural polyphenolic compound present in numerous medicinal herbs has been reported to delay the nuclear transport of viral particles to the nucleus, by decreasing the expression of dynein within the cell. Cells treated with PGG showed accumulated capsids in the cytoplasm when staining the capsid protein VP5 (Jin et al, 2016 ).…”
Section: Capsid Transport To the Nucleus And Genome Delivery Into Thimentioning
confidence: 99%
“…Interestingly, pentagalloylglucose (PGG), a natural polyphenolic compound present in numerous medicinal herbs has been reported to delay the nuclear transport of viral particles to the nucleus, by decreasing the expression of dynein within the cell. Cells treated with PGG showed accumulated capsids in the cytoplasm when staining the capsid protein VP5 (Jin et al, 2016 ).…”
Section: Capsid Transport To the Nucleus And Genome Delivery Into Thimentioning
confidence: 99%
“…1b). Next, the antiviral activities of Aspergillipeptide D against HSV-1/F and three ACV-resistant strains, including HSV-1/Blue, a TK mutant derived from HSV-1, and two clinical HSV-1 strains HSV-1/106 and HSV-1/153 [19], were monitored by plaque reduction assay (Fig. 2), which clearly showed that Aspergillipeptide D inhibits both HSV-1/F and ACV-resistant strains infection in a dose-dependent manner.…”
Section: Resultsmentioning
confidence: 99%
“…PGG, as a hydrolyzable phenolic compound, has been found to exert an antiviral effect on several viruses by diverse mechanisms, such as blocking the cell entry of hepatitis C virus (51) and inhibiting the replication of varicella-zoster virus (VZV) by suppression of JNK activation and the viral immediate early 62 protein (52). It has also been reported to inhibit herpes simplex virus 1 (HSV-1) infection by blocking nuclear transport and the process of nucleocapsid egress via inhibition of dynein and disruption of the cellular localization of UL31/UL34 (53). Additionally, some studies have revealed that PGG exerts anti-HSV activity by inducing mTOR-dependent autophagy (54) or by downregulating cofilin 1 (4).…”
Section: Discussionmentioning
confidence: 99%